Building the Brand Image of Demak as a Center for Religious Tourism Destinations through Brand Development and e-WOM - Anita Septiani Rosana; Saifudin Saifudin (An-Nida : Jurnal Komunikasi Islam, 2022)
This paper aims to investigate the factors that influence the brand image of a destination. This research examines the impact of destination brand awareness, brand quality, and e-WOM on destination brand image. The sample data used in this study were 112 respondents from 7 provinces in Indonesia. Multiple linear regression was used to test the significance of the effect of the independent variable on the dependent variable. The results of the IBM SPSS 25 test show that the destination and the quality of the destination brand can affect the destination's brand image; on the other hand, e-WOM cannot. Tour service providers can predict tourist behaviour through this paper. As for academics, this paper can be used for further research by integrating branding strategies as predictors of the destination image. Empirically this research helps improve understanding of how to communicate a brand in a destination.